Impact of a Bacterial Volatile 2,3-Butanediol on Bacillus subtilis Rhizosphere Robustness - Yi, Hwe-Su; Ahn, Yeo-Rim; Song, Geun C.; Ghim, Sa-Youl; Lee, Soohyun; Lee, Gahyung; Ryu, Choong-Min (Frontiers in Microbiology, 2016)
Volatile compounds, such as short chain alcohols, acetoin, and 2,3-butanediol, produced by certain strains of root-associated bacteria (rhizobacteria) elicit induced systemic resistance (ISR) in plants. The effects of bacterial volatile compounds (BVCs)on plant and fungal growth have been extensively studied; however, the impact of bacterial BVCs on bacterial growth remains poorly understood. In this study the effects of a well-characterized bacterial volatile, 2,3-butanediol, produced by the rhizobacterium Bacillus subtilis, were examined in the rhizosphere. The nature of 2,3-butanediol on bacterial cells was assessed, and the effect of the molecule on root colonization was also determined. Pepper roots were inoculated with three B. subtilis strains: the wild type, a 2,3-butanediol overexpressor, and a 2,3-butanediol null mutant. The B. subtilis null strain was the first to be eliminated in the rhizosphere, followed by the wild-type strain. The overexpressor mutant was maintained at roots for the duration of the experiment. Rhizosphere colonization by a saprophytic fungus declined from 14 days post inoculation in roots treated with the B. subtilis overexpressor strain. Next, exudates from roots exposed to 2,3-butanediol were assessed for their impact on fungal and bacterial growth in vitro. Exudates from plant roots pre-treated with the 2,3-butanediol overexpressor were used to challenge various microorganisms. Growth was inhibited in a saprophytic fungus (Trichoderma sp.), the 2,3-butanediol null B. subtilis strain, and a soil-borne pathogen, Ralstonia solanacearum. Direct application of 2,3-butanediol to pepper roots, followed by exposure to R. solanacearum, induced expression of Pathogenesis-Related (PR) genes such as CaPR2, CaSAR8.2, and CaPAL. These results indicate that 2,3-butanediol triggers the secretion of root exudates that modulate soil fungi and rhizosphere bacteria. These data broaden our knowledge regarding bacterial volatiles in the rhizosphere and their roles in bacterial fitness and as important inducers of plant defenses.